2016
DOI: 10.3138/cjccj.2015.e19
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship: A Missing Piece to Manage Juvenile Intensive Supervision Programs and Youth Gangs?

Abstract: Intensive supervision probation (ISP) has proven generally ineffective for youth. In this article we argue that mentorship, an intervention with increasing empirical support in the literature, is a missing treatment component. We test this proposition with results from the Spotlight Serious Offender Services Unit, an urban-based Canadian ISP program that targets high-risk gang youth. Unique to Spotlight is their adoption of street mentors to work with youth in the community. Our study incorporated quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Therefore, while it is important to provide and increase access to trauma-focused interventions, it is also important to identify and support the basic needs of gang-involved youth such as physical health, emotional support, and safety. One way to address these needs and reduce youth's trauma exposure is encouraging desistance from gang involvement, and many gang interventions have been successful in doing so (Boxer, Docherty, Ostermann, Kubik, & Veysey, 2017;Sexton & Turner, 2011;Weinrath, Donatelli, & Murchison, 2016). However, the current work further supports the need for gang intervention programming to include trauma-informed practices and trauma-focused interventions (Dierkhising & Kerig, 2018) to address these basic needs and behavioral health in an integrated fashion.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, while it is important to provide and increase access to trauma-focused interventions, it is also important to identify and support the basic needs of gang-involved youth such as physical health, emotional support, and safety. One way to address these needs and reduce youth's trauma exposure is encouraging desistance from gang involvement, and many gang interventions have been successful in doing so (Boxer, Docherty, Ostermann, Kubik, & Veysey, 2017;Sexton & Turner, 2011;Weinrath, Donatelli, & Murchison, 2016). However, the current work further supports the need for gang intervention programming to include trauma-informed practices and trauma-focused interventions (Dierkhising & Kerig, 2018) to address these basic needs and behavioral health in an integrated fashion.…”
Section: Discussionmentioning
confidence: 76%
“…These two examples highlight the importance of not only conducting a thorough search but also the importance of following the criteria defined for critically appraising studies once they are found. Importantly, Weinrath et al’s (2016) study appears to be driving the difference in findings between our Olsson et al’s (2021) study and the DuBois (2022) brief comment regarding studies based on nonrandomized controlled trials. As such, had DuBois (2022) chose to exclude Weinrath et al (2016), the findings they present in their brief comment would likely have been similar to our findings.…”
Section: Systematic Critical Appraisalmentioning
confidence: 77%
“…Importantly, Weinrath et al’s (2016) study appears to be driving the difference in findings between our Olsson et al’s (2021) study and the DuBois (2022) brief comment regarding studies based on nonrandomized controlled trials. As such, had DuBois (2022) chose to exclude Weinrath et al (2016), the findings they present in their brief comment would likely have been similar to our findings.…”
Section: Systematic Critical Appraisalmentioning
confidence: 77%
See 1 more Smart Citation
“…but increased convicted offenses (e.g., convictions, adjudications, incarcerations; Bouchard & Wong, 2018). On the other hand, one study of a more recent ISP program for juvenile gang offenders in Manitoba, Canada that included a mentorship component (not included in the aforementioned reviews) successfully reduced recidivism compared to usual probation services (Weinrath, Donatelli, & Murchison, 2016). The mixed evidence suggests it is not clear whether combining treatment services with intensive supervision for juveniles is an effective model.…”
Section: Intensive Aftercare Program: Las Vegas Nv (1995-2000)mentioning
confidence: 99%